2015
DOI: 10.14202/vetworld.2015.46-51
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock proteins: a therapeutic target worth to consider

Abstract: Heat shock proteins (HSPs) are the molecular chaperones, that are not only expressed during the normal growth process of cell cycle consecutively, but also get induced in cells during various stress conditions produced by cellular insult, environmental changes, temperature, infections, tumors etc. According to their molecular weight and functions, HSPs are divided into five major families. HSP90, HSP70, HSP60 and HSP100 are the most studied members of the family. Experimental studies have proved that overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 59 publications
0
33
0
4
Order By: Relevance
“…Heat shock protein genes ( HSPA5, HSPA6, HSPA8, HSP90AA1, HSP 70.1 ), found between the highly expressed genes in the lactation, have a protective function, allowing cells to survive lethal conditions, and also interact with various components of the programmed cell death machinery; on the other hand, membrane bound HSPs mediate immunological functions [97, 98]. Our finding confirms what reported in literature about HSP functions and demonstrates how MSCs, in goat colostrum, can support a high level of protein synthesis act to operate in both immunity and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock protein genes ( HSPA5, HSPA6, HSPA8, HSP90AA1, HSP 70.1 ), found between the highly expressed genes in the lactation, have a protective function, allowing cells to survive lethal conditions, and also interact with various components of the programmed cell death machinery; on the other hand, membrane bound HSPs mediate immunological functions [97, 98]. Our finding confirms what reported in literature about HSP functions and demonstrates how MSCs, in goat colostrum, can support a high level of protein synthesis act to operate in both immunity and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, increased expression of heat shock protein 70 (HSP70) is seen in the ischemic penumbra, signifying its role in the attenuation and protection of ischemia. Dubey et al, using cerebral ischemia mice models, showed overexpressing HSP70 protected against myocardial and cerebral ischemia (MCA occlusion); preconditioning with ischemia showed enhanced expression of HSP70 in the cell ( 113 ).…”
Section: Mechanisms Of Limb Remote Ischemic Pre- Per- and Postcondimentioning
confidence: 99%
“…Unterstützt wird diese Annahme dadurch, dass überlebende neuronale Zellen oftmals HSPs überexprimieren. Die erhöhte Expression von HSP70 in Tiermodellen von Morbus Parkinson und Morbus Alzheimer führte durch eine Reduktion des durch Caspase-3 induzierten Zelltodes zu einer Reduktion der krankheitstypischen Symptome [45]. Für den klinischen Einsatz von protektiven HSPs gibt es bisher nur wenige Beispiele.…”
Section: Hitzeschockproteine Als Zukünftiger Therapieansatzunclassified